2006
DOI: 10.1158/0008-5472.can-06-0157
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Peroxiredoxin 2 and Aberrant Methylation of 33 CpG Islands in Putative Promoter Regions in Human Malignant Melanomas

Abstract: Aberrant methylation of promoter CpG islands (CGI) is involved in silencing of tumor suppressor genes and is also a potential cancer biomarker. Here, to identify CGIs aberrantly methylated in human melanomas, we did a genomewide search using methylation-sensitive representational difference analysis. CGIs in putative promoter regions of 34 genes (ABHD9,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
127
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(137 citation statements)
references
References 24 publications
8
127
0
2
Order By: Relevance
“…These deletions involve many genes that were earlier reported to be frequently lost by deletion, mutation or promoter methylation events in various solid tumours and acute leukaemia, such as ETV6 (12p13), SLIT2(4p15), AUTS2(7q11), NF1(17q12), MSH5 (6p21), MSH3(5q), HUS1(7p12), CDKN2D(19p13.2), WISP-1(8q24), IDE or TLX2(2p13.1). 14,[16][17][18][19][20][21][22][23][24] These genes are involved in major cellular processes, including DNA repair (MSH3, MSH5, HUS1), cell cycle regulation (HUS1, CDKN2D) and the RAS pathway (NF1). Another gene, IDE (10q32), a putative tumour suppressor insulin degrading enzyme, may play a role as a RB protector by preventing inactivation of RB1.…”
Section: Discussionmentioning
confidence: 99%
“…These deletions involve many genes that were earlier reported to be frequently lost by deletion, mutation or promoter methylation events in various solid tumours and acute leukaemia, such as ETV6 (12p13), SLIT2(4p15), AUTS2(7q11), NF1(17q12), MSH5 (6p21), MSH3(5q), HUS1(7p12), CDKN2D(19p13.2), WISP-1(8q24), IDE or TLX2(2p13.1). 14,[16][17][18][19][20][21][22][23][24] These genes are involved in major cellular processes, including DNA repair (MSH3, MSH5, HUS1), cell cycle regulation (HUS1, CDKN2D) and the RAS pathway (NF1). Another gene, IDE (10q32), a putative tumour suppressor insulin degrading enzyme, may play a role as a RB protector by preventing inactivation of RB1.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we analyzed the methylation status of 13 candidate tumor suppressor genes, RASSF1A, RASSF2A, SOCS1, CASP8, NORE1A, RUNX3, RIZ1, BLU, HOXA9, HOXB5, p16INK4A, p14ARF and DCR2, by conventional MSP. [13][14][15][16][17][18][19][20][21][22] These genes have previously been shown to be aberrantly methylated in various adult and childhood cancers and also represent important elements for several signaling pathways and cell cycle regulation (Table IV). We found that 3 genes, RASSF1A, SOCS1 and CASP8, were methylated in a substantial number of hepatoblastoma tumors.…”
Section: Discussionmentioning
confidence: 99%
“…9,27 The genes examined were RASSF1A, RASSF2A, NORE1A, SOCS1, CASP8, RUNX3, RIZ1, BLU, HOXA9, HOXB5, p16INK4A, p14ARF and DCR2. [13][14][15][16][17][18][19][20][21][22] The primer sequences and their location in the original genomic sequences are listed in Table I, and the location of the analyzed fragments for RASSF1A, SOCS1 and CASP8 are shown in Figure 1a. While the primer sequences of RASSF1A are located in the promoter region, those of CASP8 and SOCS1 are derived from the exon 4-intron 4 region and the exon 1, respectively, because the methylation status of these regions is correlated with the expression.…”
Section: Patients and Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Epigenetic silencing of ARF through hypermethylation leads to loss of p53-mediated apoptosis and to melanoma progression. 29 van der Velden 30 reported hypermethylation of the INK4A promoter in 32% of primary uveal melanomas and 50% of uveal melanoma cell lines, while in many cases ARF was not affected. 30 Straume et al 28 reported loss of p16 protein expression by hypermethylation of the CDKN2A promoter in 19% of primary cutaneous melanomas and in 33% of metastases.…”
Section: Rassf1amentioning
confidence: 99%